An Oddi tumor case treated by endoscopic papillectomy - Fatih HİLMİOĞLU and Murat ALADAĞ and Vildan TAŞKIN and Melih KARINCAOĞLU and Bülent MİZRAKİ and; nt YILDIRIM (Turkish Journal of Gastroenterology, 2019)
-